Analysis of the influence of side linking son in concrete wall buildings - Henrique Meneses, Paulo; Puel, André; Lima de Oliveira, Alexandre; Toppan Rabello, Fernando (Seven Editora, 2023)
The current regulations, NBR 16055:2012, defines concrete wall as self-supporting structural element, molded in loco, in which it contains a length greater than ten times its thickness, being able to withstand load in the same plane of the wall. In addition to Brazilian regulations there are several international codes, such as ACI 318:2019 - Building Code Requirements for Structural Concrete, and The Australian AS 3600:2009 - Concrete Structures. Each standard has its own formulation for calculating the strength of the concrete wall element. The Brazilian code and the Australian code converge in relation to adopting the contribution of lateral links to wall resistance. The North American code mentions only the top-base links. Similarly the structures in Structural Masonry, the walking of vertical loads can occur on the surface of the wall element, being possible to use the calculation models consolidated in structural masonry bibliographies (PIS, GIP and MPT), making this study valid for structural analysis of these two systems. Throughout this work, the results of the requesting efforts of each procedure were calculated and analyzed. Later, with the help of commercial software SAP2000, a structure was launched using the Three-Dimensional Portico Model, performing their respective numerical analyses. At the end of these analyses, it was possible to observe that the model without interactions between walls was able to satisfactorily perform the distribution of efforts for the structures adopted in this study, when compared with models with interaction between walls and numerical. DOI: https://doi.org/10.56238/tfisdwv1-034